Propylthiouracil-induced agranulocytosis as a rare complication of antithyroid drugs in a patient with Graves’ disease - Rabelo,Patrícia Novais (2019)
SUMMARY INTRODUCTION: Graves’ disease (GD) is an autoimmune disorder characterized by hyperthyroidism. Antithyroid drugs (ATDs) are available as therapy. Agranulocytosis is a rare but potentially fatal complication of this therapy. In this study, we report agranulocytosis induced by propylthiouracil (PTU) in a patient with GD and the difficulties of clinical management. CASE: RNBA, male, 30 years old, with GD, treated with propylthiouracil (PTU). He progressed with pharyngotonsillitis. Then, PTU was suspended and antibiotic, filgrastim, propranolol, and prednisone were initiated. Due to the decompensation of hyperthyroidism, lithium carbonate, dexamethasone, and Lugol's solution were introduced. Total thyroidectomy (TT) was performed with satisfactory postoperative progression. DISCUSSION: We describe here the case of a young male patient with GD. For the treatment of hyperthyroidism, thioamides are effective options. Agranulocytosis induced by ATDs is a rare complication defined as the occurrence of a granulocyte count <500/mm3 after the use of ATDs. PTU was suspended, and filgrastim and antibiotics were prescribed. Radioiodine (RAI) or surgery are therapeutic alternatives. Due to problems with ATD use, a total thyroidectomy was proposed. The preoperative preparation was performed with beta-blocker, glucocorticoid, lithium carbonate, and Lugol solution. Cholestyramine is also an option for controlling hyperthyroidism. TT was performed without postoperative complications. CONCLUSION: Thionamide-induced agranulocytosis is a rare complication. With a contraindication to ATDs, RAI and surgery are definitive therapeutic options in GD. Beta-blockers, glucocorticoids, lithium carbonate, iodine, and cholestyramine may be an adjunctive therapy for hyperthyroidism.